Livestock waste management to improve community knowledge in the cow farming groups - Syarifah Farradinna; Elfis Elfis; Rafil Arizona; Jhonni Rachman; Prima Wahyu Titisari (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
The Wong Cilik Animal Husbandry Group is still struggling with traditional waste treatment, which pollutes the air and soil. The goal of indoctrination is to educate and encourage livestock farmer groups to be proactive in controlling, overcoming, and making decisions regarding cow manure waste. Furthermore, this activity aims to strengthen the Wong Cilik Farm Community Group's capacity to use cow manure through teaching and encouragement. Several experts from the fields of machinery, agriculture, and psychology participated in this activity. Participants were given a pre-test and a post-test before and after socialization. The results of the pre-test and post-test indicated that the activity’s objectives of increasing the community’s knowledge about livestock waste management were met. The community is finally aware that livestock manure can be used to convert the residual biogas waste into manure. Through this socialization, the community learns that cow manure waste can be turned into products with high value.